Marketing Strategy Analysis at Kompas Gramedia Xpress (KGX) Bandung Branch - Shafira Tiara Rachmawati; Erna Maulina; Tetty Herawaty (Dinasti Publisher, 2025)
The increasingly competitive logistics industry requires companies to implement appropriate marketing strategies. Kompas Gramedia Xpress (KGX) Bandung, as a technology-based logistics service provider, needs to evaluate its marketing strategies to remain relevant to market demands. This study aims to analyze the implementation of Segmenting, Targeting, Positioning (STP) and the 7P Marketing Mix at KGX Bandung, as well as identify challenges in its implementation. This research employs a descriptive qualitative method with data collected through interviews, observations, and document analysis. The findings indicate that KGX Bandung targets Business-to-Business (B2B) customers, positioning itself as a reliable logistics partner offering technology-based services. The 7P Marketing Mix is effective in terms of product, place, process, and physical evidence, while promotion and human resources require further optimization.